(untitled) (Comillas Journal of International Relations, 2019)
Since the seventies there has been an intensification of the links between the Socialist International (SI) and similar organizations in Latin America. The wave of dictatorships that evoked memories of fascism awakened solidarity with and interest in what was happening on the other side of the Atlantic. Those were also the years in which the Socialist International produced a series of formulations regarding international matters, which were put into practice by the government of Felipe González in Spain. Under his leadership, Spain defined a new foreign policy towards Latin America. However, his original economic postulates had to vary because of the accession to the European Economic Community (EEC). This barely researched chapter of history is very important because it constitutes the foundation on which the entire framework that currently governs Euro-Latin American relations was built.